Pondok Pesantren Sebagai Warisan Klasik Dalam Pembentukan Karakter Anak Usia Dini Di Era Digital - Novitasari, Nurul (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2025)
This study aims to describe the implementation of classical pesantren (Islamic boarding school) values in shaping the character of early childhood learners and to examine strategies for integrating these values with technology-based learning at TK Muslimat NU 33 Binangun, Singgahan, Tuban. The research employed a descriptive qualitative approach, using data collection techniques such as observation, in-depth interviews, and documentation. The subjects included the principal and classroom teachers, while the research objects covered the application of pesantren values such as ta’dzim (respect), discipline, spirituality, and independence within the context of early childhood education in the digital era. The findings indicate that classical pesantren values are implemented through habituation activities such as Friday infaq (charity), congregational Dhuha prayer, greeting teachers every morning, sharing with friends, learning to recite using the Iqro’ method, and celebrating Islamic holidays (PHBI). These activities foster religious, disciplined, empathetic, and socially responsible character traits in children. Moreover, the school successfully integrates pesantren values with digital technology through the use of media such as laptops for showing Islamic stories and educational videos. In conclusion, the integration of classical pesantren values and digital innovation forms a contextual, relevant, and effective model of character education for early childhood learners. This model serves as a strategic alternative to preserve traditional Islamic values while adapting to the challenges of the digital era.